2019
DOI: 10.1002/anr3.12007
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscope‐assisted flexible intubation tracheal tube exchange in a patient with a difficult airway

Abstract: An 88-year-old woman presented with acute airway obstruction caused by a large retrothyroid bleed following anterior neck trauma. Her airway was secured in the operating theatre with an awake nasal flexible optical bronchoscope tracheal intubation using an Intubating Laryngeal Mask Airway tracheal tube. Haemostasis was achieved following surgical ligation and the patient was transferred to the critical care unit. Postoperatively, a large leak around the tracheal tube was noted and a decision was made to change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Saunders et al described videolaryngoscopy-assisted flexible intubation in the context of exchanging ETT, highlighting the significance of combining techniques to maintain a visible airway throughout the procedure. 11 Greib et al successfully performed tracheal intubation on 16 patients using a VLS and a flexible bronchoscope. 12 Young et al reported a case of successful airway management using a McGrath MAC VLS and a flexible bronchoscope in a morbidly obese patient with large goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Saunders et al described videolaryngoscopy-assisted flexible intubation in the context of exchanging ETT, highlighting the significance of combining techniques to maintain a visible airway throughout the procedure. 11 Greib et al successfully performed tracheal intubation on 16 patients using a VLS and a flexible bronchoscope. 12 Young et al reported a case of successful airway management using a McGrath MAC VLS and a flexible bronchoscope in a morbidly obese patient with large goiter.…”
Section: Discussionmentioning
confidence: 99%
“…Videolaryngoscopy is used universally and after 5 yr we believe that we are still learning new skills and benefitting our patients. 27 We removed all first-generation SGAs from use 3 yr ago (except for flexible laryngeal masks for head and neck surgery) and have only two types of second-generation SGA available for routine (and rescue) use. Point-of-care eFONA kits (a scalpel, a bougie, and a tracheal tube) are boxed and available in every location where anaesthesia takes place.…”
Section: Plan D and Standardisationmentioning
confidence: 99%
“…Saunders et al. are the first to describe a novel approach to videolaryngoscope‐assisted flexible intubation tracheal tube exchange, which, using a combination of several simple techniques, ensures the airway remains secure and visible throughout . They provide an excellent recipe to navigate this challenging scenario which will be of use to all clinicians.…”
Section: Airway Managementmentioning
confidence: 99%